1976
DOI: 10.1148/119.3.554
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Calcification in Mixed Papillary and Follicular Carcinoma of the Thyroid Gland

Abstract: An unusual egg-shell calcification was found in the thyroid gland on a routine radiograph. The 99mTc-pertechnetate thyroid image showed a cold nodule in the inferior pole of the left lobe which proved to be mixed papillary-follicular carcinoma. There was no characteristic pattern of calcification in the thyroid gland which would permit precise diagnosis of cancer; however, psammomatous calcification frequently occurs in papillary carcinoma of the thyroid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
17
0
1

Year Published

1978
1978
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 2 publications
1
17
0
1
Order By: Relevance
“…However, there is no reliable classification for distinguishing malignant from benign. Calcification of a thyroid nod- reported not only in cases of papillary carcinoma [15] and but also in undifferentiated carcinoma [16]. In our study, 5.9% of malignant thyroid nodules had the annular type of calcifications.…”
Section: Discussionsupporting
confidence: 46%
“…However, there is no reliable classification for distinguishing malignant from benign. Calcification of a thyroid nod- reported not only in cases of papillary carcinoma [15] and but also in undifferentiated carcinoma [16]. In our study, 5.9% of malignant thyroid nodules had the annular type of calcifications.…”
Section: Discussionsupporting
confidence: 46%
“…However, cases of papillary, undifferentiated, and follicular carcinomas associated with this type of calcification have recently been reported. [17][18][19] Taki et al 9 reported that 43% (6/14) of peripheral calcifications were associated with malignancy, and all of the malignant lesions identified were papillary carcinomas. Although FNA is a very good diagnostic tool with a sensitivity of 71-93% and a specificity of 96%, 15,20 the obtention of diagnostic material from a calcified nodule is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…It was generally thought to be more frequently associated with benignity 23 ; however, cases of papillary thyroid carcinoma associated with this type of calcification have been reported. 20,24 Pathologic correlation was available for all nodules with peripheral calcification in our series. Pathologic examination of these nodules showed extensive areas of dystrophic calcification, which were associated or not associated with malignant cells.…”
mentioning
confidence: 99%